A case series of diverse cardiac abnormalities in collegiate athlete with COVID-19: role for multimodality imaging - Turpin, V. R. G.; Goerl, K.; Chow, C. H.; Ade, C. J. (Case Reports in Cardiology, 2022)
Introduction. Since the COVID-19 pandemic there is concern for subclinical cardiac pathology in the absence of clinical symptoms in collegiate athletes, we present 4 cases of abnormal left ventricular global longitudinal strain (LVGLS), a "red-flag" for potential COVID-19 myocardial disease, following diagnosis with diverse abnormalities reported via multimodality imaging weeks into recovery. Methods. Cardiac imaging studies consisting of transthoracic echocardiography (TTE) and cardiovascular magnetic resonance imaging (CMR) were performed 10 days post-COVID-19 diagnosis and several weeks into recovery. Results. Initial TTE revealed abnormal left ventricular global longitudinal strain (LVGLS), an identified "red-flag" for potential COVID-19 myocardial disease. Further CMR imaging revealed potential recent/prior myocarditis in 1 athlete. Follow-up TTE several weeks later revealed a return to normal LVGLS. Conversely, 2 cases with normal CMR imaging had a LVGLS that remained abnormal >30 days into recovery. Conclusions. These individual cases highlight the substantial differences in echocardiographic and CMR abnormalities between athletes with confirmed COVID-19.